Rossetti’s Bocca Baciata (1859) and the Ideals of the Early Phase of the Pre-Raphaelite Movement - Mohammed, Zhino Jabbar (Sulaimani Journal for Humanities, 2018)
This paper is about Dante Gabriel Rossetti’s (1828-1882) double work of art Bocca Bacciata (1859) that is a double work of art (a painting attached to a poem.) Among Rossetti’s other double works of art, Bocca Baciata (1859) is remarkable for its intensely sensual quality. This paper is significant in the field of the Pre-Raphaelite Art and Literary Movement in the context of mid-Victorian art and literature. It will contribute to both fields of Pre-Raphaelitism and Symbolism of the mid-Victorian paintings and poetry in England. This paper answers the following questions: to what extent was Rossetti’s Bocca Bacciata identified as a turning point in British Art and his own poetic style? How images of women were depicted in the first and second phases of the Pre-Raphaelite movement? What were the Pre-Raphaelite principles according to John Ruskin’s theory? Did Rossetti’s Bocca Baciata follow those principles or oppose them? Why? Using the theory of Symbolism to analyze both the poem and the painting we will reach to the findings of the paper that to a great extent the double work has been regarded as a shift from a spiritual muse to a sensual object. Also, the study provides a clearer understanding of the way Rossetti’s paintings and poems became a turning point in the nineteenth-century British Art and his own poetic style. The findings of this study would be beneficial for the students and researchers of the literary and cultural studies, departments of English, British Literature studies and art history.
Keywords: PreRaphaelite literary and art movement double works of art symbolism TheKissed Mouth